Visas and work permits : possible global negotiating initiatives - Chi-Yung Ng; John Whalley (Center for Economic Studies and ifo Institute (CESifo), 2005)
We discuss global options for initiatives intended to ameliorate adverse impacts of visa and work permit systems used by national governments around the world. We first describe and document some of their effects, noting the relative lack of other research work on these issues. We then discuss proposals for a new and supplemental global visa structure which have been made as part of the Mode 4 GATS negotiations in the WTO, suggesting that the GATS/WTO may be an imperfect institutional location for negotiating on these matters. We then evaluate other approaches, including what realistically could be possible if a new body specifically created for global negotiation in the area were to be used.
Keywords: F22; J61; J71; D78; O24; 330; Einwanderungsrecht; Internationale Arbeitsmobilität; GATS; Verhandlungen; Organisation; Welt; Arbeitserlaubnis; Mode 4